Description of five new species of the genus Stigmaeus Koch (Acari: Raphignathoidea: Stigmaeidae) from Turkey - Doğan, Si̇bel; Doğan, Sali̇h; Erman, Orhan (Zootaxa, 2017)
Five new species of Stigmaeidae (Acariformes: Raphignathoidea) from Harşit Valley and Örümcek Forests (Turkey) are described: Stigmaeus communis sp. nov., S. fimus sp. nov., S. harsitensis sp. nov., S. longiclipeatus sp. nov., and S. pseudoparmatus sp. nov.